2014
DOI: 10.1002/2014jc009909
|View full text |Cite
|
Sign up to set email alerts
|

Impact of measurement uncertainties on determination of chlorophyll‐specific absorption coefficient for marine phytoplankton

Abstract: Understanding variability in the chlorophyll-specific absorption of marine phytoplankton, a ph * Chl (k), is essential for primary production modelling, calculation of underwater light field characteristics, and development of algorithms for remote sensing of chlorophyll concentrations. Previous field and laboratory studies have demonstrated significant apparent variability in a ph * Chl (k) for natural samples and algal cultures. However, the potential impact of measurement uncertainties on derived values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…In our culture experiment, we found significant negative correlations between a à ph ð440Þ, a à ph ð675Þ and Chla concentration of both phytoplankton species although neither were affected by non-phytoplankton particles (Figure 8), which were widely found in other studies (Bricaud et al 1995;McKee et al 2014;Pandi et al 2014;Yl€ ostalo et al 2014). Some field studies attributed the significant negative correlation to the package effects by non-phytoplankton particles (Bricaud et al 1995;Mill an-N uñez & Mill an-N uñez 2010).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our culture experiment, we found significant negative correlations between a à ph ð440Þ, a à ph ð675Þ and Chla concentration of both phytoplankton species although neither were affected by non-phytoplankton particles (Figure 8), which were widely found in other studies (Bricaud et al 1995;McKee et al 2014;Pandi et al 2014;Yl€ ostalo et al 2014). Some field studies attributed the significant negative correlation to the package effects by non-phytoplankton particles (Bricaud et al 1995;Mill an-N uñez & Mill an-N uñez 2010).…”
Section: Discussionsupporting
confidence: 76%
“…Some field studies attributed the significant negative correlation to the package effects by non-phytoplankton particles (Bricaud et al 1995;Mill an-N uñez & Mill an-N uñez 2010). However, a large proportion of apparent variability in a à ph ðλÞ and significant negative correlations between a à ph ðλÞ and Chla concentration could be attributed to measurement uncertainties (McKee et al 2014). In addition, some studies have shown the package effect was not present when a à ph ð675Þ was 0.02 À 0.03 m 2 /mg Chla (Johnsen et al 1997;Stramski et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Absorption by phytoplankton, a ph ( λ ), was determined by bleaching samples, measuring the absorption of nonalgal particles, a NAP ( λ ), and subtracting this from a p ( λ ). Path length amplification factors and scattering offset corrections were determined using a linear regression approach (Lefering et al, ; McKee et al, ) and corresponding PSICAM a p ( λ ) data. The resulting filter pad corrections were subsequently applied to both bleached and unbleached filter pad absorption spectra.…”
Section: Methodsmentioning
confidence: 99%
“…This has led some authors to determine the SIOPs based on (1) multiple linear regression of total IOPs against constituent concentrations (Brown et al, ; Strömbeck et al, ), (2) simple linear regression for data sets partitioned by optically dominant constituent (McKee & Cunningham, ), or (3) laboratory analysis of phytoplankton cultures (Bricaud et al, ; Stramski & Morel, ) and purified suspended minerals (Babin & Stramski, ). The linear regression analysis proposed by McKee and Cunningham () allows calculation of representative SIOPs for a specific location and is attractive as the method reduces the impact of systematic and random errors (McKee et al, ). These authors used relationships between IOPs to identify optically distinct water types dominated by different constituents ( Chl or MSS ) in the studied area, which allowed the application of regression analysis to partitioned IOPs and single constituent concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…CDOM absorption (m −1 ) exponentially decreases with longer wavelengths and a biooptical model for spectral CDOM is often based on a measurement at approximately 440 nm. The equations for a cdom and phytoplankton absorption (a ph ) are commonly used models to describe CDOM in case-2 waters and phytoplankton absorption in case-1 waters (Gilerson et al 2008;Brewin et al 2011;McKee et al 2014). Usually, the shape factor S of the exponential decrease ranges from 0.005 nm −1 to 0.031 nm −1 (Brewin et al 2015;Bricaud et al 2012;Chen et al 2017) and the reference is usually set to an available blue wavelength (440 nm).…”
Section: Bio-optical Modelsmentioning
confidence: 99%